MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR IPA MENGGUNAKAN KELAS DIGITAL EDMODO - Lilis Indayani Suprapto (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
The quick advancement of information and communication technology ought to be able to boost educational efforts and results. It is anticipated that the availability of digital classrooms would serve as a bridge connecting students and teachers in teaching and learning activities without needing to be restricted by time or space. In semester 1 of the Human Reproductive System course for Class IX G of SMP Negeri 10 Probolinggo undertook this classroom action research. The Edmodo application is used in this project to deliver digital classes. The outcomes demonstrated that the use of digital classrooms increased student engagement and achievement. During the transition to digital classes, students were extremely engaged, enthusiastic, and active. Based on their responses to the researcher's Interest Questionnaire after the introduction of the digital class, all of the students indicated that they planned to continue their education there and that other subjects would also benefit from the use of the digital class.Keywords: science, exercise, learning achievement, and digital classes